Location of VirD4 protein of Anaplasma marginale in infected erythrocytes by specific serum by immunofluorescence - Barrera-Molina, América Ivette; Rodríguez-Camarillo, Sergio D (Ecosistemas y Recursos Agropecuarios, 2020)
By analyzing the genome of Anaplasma marginale, proteins of the type IV secretion system, involved in the transfer of substrates between bacteria and other organisms, have been identified. In other bacterial models the VirD4 protein of this system is associated with the translocation of proteins and complexes involved in the interaction with their host cells, indicating that in A. marginale this protein might be associated with the invasion and survival within the erythrocyte. For these reasons the objectives of the present study were: the analyisis by bioinformatic tools of the degree of conservation of the VirD4 protein between different Mexican strains, and the detection of this protein in infective forms of A. marginale in bovine erythrocytes. The analysis of the nucleotide and amino acid sequences of VirD4 showed 100% identity between the products. The branched synthetic peptide designed based on the analysis reacted with sera from immune and infected cattle using ELISA assays. Specific antibodies against MAP-VirD4 reacted by indirect immunofluorescence with initial bodies of intraerythrocytic A. marginale. With these findings we infer that VirD4 is a conserved protein that is apparently expressed during the invasion of erythrocytes or is an important element during infection, which indicates that the peptide could be considered as a possible vaccine candidate against bovine anaplasmosis.